Anti-Ovipositor Power of Jayanti Plant (Sesbania sesban) for Integrated Control of Cabbage Pest (Plutella xylostella) - Suripto Suripto; Hilman Ahyadi; Rachmawati Noviana Rehayu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Cabbage harvest failure is often caused by failure to control cabbage pests. Cabbage pest control by eradicating Plutella xylostella larvae is considered less effective because the cabbage plant has been damaged due to infection with P. xylostella eggs and larvae. Thus, the control target needs to be shifted to prevent P. xylostella amago from laying eggs (ova-positioning) on cabbage plants. This study aims to determine the anti-ovipositor power of Sesbania sesban leaf extract against P. xylostella. The leaves of S. sesban were air-dried and then ground. The dry powder (simplicia) of S. sesban leaves was extracted with water as the sole solvent. The water-extract of S. sesban leaves was tested for anti-ovipositor against P. xylostella in situ on cabbage plants according to a completely randomized block design. Experimental groups were made according to variations in extract concentration. Complete randomization was carried out on experimental units in each group according to the variation in the length of exposure to the extract before access to the ovipositor was opened (Cages were opened after 1,2,3,4,5 and 6 days from the time of extract spraying). Each experimental unit consisted of 4 cabbage plants as replicates. The treatment was given by spraying a solution of S. sesban leaf extract with a concentration according to the group evenly on the entire leaf surface of each cabbage plant. The observed research variable was the number of P. xylostella eggs per cabbage plant after the cage of cabbage plant unit was opened. The results showed that the leaf extract of S. sesban could inhibit P. xylostella as an ovipositor to lay its eggs on cabbage plants effectively for up to three days. With concentrations of 1.83 to 2.14 ppm, the aqueous extract of S. sesban leaves did not inhibit P. xylostella egg laying, but with concentrations of 478.63 to 1283.88 ppm it could inhibit 50 to 100%.